Problema dimensionale e politica industriale: gli incentivi governativi alle fusioni - Bigazzi, Sabrina; Mangani, Andrea (Piccola Impresa / Small Business, 2010)
This paper examines the recent government interventions that have been adopted in Italy to promote directly the growth of firms. The merger incentives present some common characteristics, such as the absence of destination sectors, and some differences, regarding, for example, the identity of the beneficiaries. The analysis and the comparison of the incentives are conducted considering the actual Italian industrial structure, its results and the debate concerning the best modes of economic development. On the one hand, the incentives are apparently unable to contrast the basic causes of the small size of firms, on the other they reveal different approaches to tackle the “dimensional issue”, once more in discussion given the increased level of international competition